Evaluation of salinity effect on quantitative analysis of aquatic humic substances using nonionic DAX-8 resin. (March 2016) - Kida, Morimaru; Ohtsuka, Toshiyuki; Kato, Taku; Suzuki, Takeshi; Fujitake, Nobuhide
Abstract: A nonionic macroporous resin, Amberlite ® XAD-8, or its substitute, Supelite™ DAX-8, is used when isolating or quantifying aquatic humic substances (AHS). However, the effect of salinity on the adsorption behavior of AHS onto the resin is yet to be confirmed, rendering the possibility of salinity-induced changes in the values of quantified amounts or characteristics of AHS obtained from a salty system. To verify the results of quantification and isolation of AHS using the resin in different salinity systems, the effect of salinity on such quantitative analyses of AHS has been examined. It has been concluded that the salinity effect is in general trivial and will not hinder comparison of results regardless of sample solution salinity. Highlights: Salinity effect on the adsorption behavior of AHS onto the DAX-8 has been examined. Salinity will not significantly affect the adsorption behavior of AHS onto the resin. Salinity will not hinder comparison of results regardless of solution salinity.